Time-restricted eating effects on performance, immune function, and body composition in elite cyclists: a randomized controlled trial - Moro, T.; Tinsley, G.; Longo, G.; Grigoletto, D.; Bianco, A.; Ferraris, C.; Guglielmetti, M.; Veneto, A.; Tagliabue, A.; Marcolin, G.; Paoli, A. (Journal of the International Society of Sports Nutrition, 2020)
Background: Although there is substantial interest in intermittent fasting as a dietary approach in active individuals, information regarding its effects in elite endurance athletes is currently unavailable. The present parallel randomized trial investigated the effects of a particular intermittent fasting approach, called time-restricted eating (TRE), during 4 weeks of high-level endurance training.